The influence of plyometric training on the impovement of special physical preparation of high-qualified visually impaired sprinters durcing pre-competition stage - Shesterova, L.; Adzhametova, L. (Slobozhanskyi herald of science and sport, 2020)
Purpose: describes the effectiveness of applying plyometric training on different flooring of highly qualified visually impaired sprinters at the pre-competition stage. Material and methods: the indicators of special physical fitness of the Honored Master of Sports of Ukraine in para-athletics among athletes with visual impairments during the pre-competition stage of the annual macro-cycle were studied. The following methods were used: analysis and generalization of scientific and methodological literature, analysis of training loads and processing of parameters of training activity, testing of the level of development of high-speed and speed-power, pedagogical observation, methods of mathematical statistics. Results: changing the flooring on which plyometric exercises were performed led to positive changes in the performance of the athlete's physical fitness. Conclusions: the use of preparation at the pre-competition stage of a highly qualified visually impaired sprinter in the six-week plyometric program contributed to a significant increase in speed and speed-power indices of the athlete (p <0.05-0.01).